Manajemen Finansial Lembaga Pendidikan Islam (Studi Tentang Optimalisasi Anggaran Pembiayaan) - Nelly Nelly (Sekolah Tinggi Agama Islam Sumatera Medan, 2021)
The education budget is often a problem in determining the quality of education, the lack of budget from the government is the main obstacle, with such a small budget, it is certainly necessary to optimize financing. The purpose of this study is to analyze the basic concepts of education financial management and optimizing the education financing budget. This research uses qualitative research methods based on literature study. The data collection method uses documentation studies, namely exploring theories or thoughts from various references. Data analysis uses content analysis, by analyzing and providing data interpretation to draw conclusions. The results of the study explain that. Sources of funds obtained by schools come from the government in the form of central and regional BOS funds, tuition fees for students, and assistance from donors, agencies, sponsors and infaq or sedekah. The available funds are then compiled in the school spending plan which is prepared by the team to be later approved by the principal and the school committee. The implementation of the school financial budget is used in accordance with the budgeted plan in an effective and efficient, trustworthy, and responsible manner. School financial accountability is reported to the directorate of school development (central BOS), the provincial education and culture office, committees, with an accountable and transparent model. The form of optimization can be realized by determining the priority scale when preparing school budgets.